The Occurrence of Tax Amnesties. Theory and Evidence - Ralph-C. Bayer; Harald Oberhofer; Hannes Winner (Austrian Institute of Economic Research (WIFO), 2014)
This paper presents a theoretical model and empirical evidence to explain the occurrence of tax amnesties. We treat amnesties as endogenous, resulting from a strategic game between many tax payers discounting future payments from punishment and a government that trades off costs and benefits of amnesty programmes. From the model we derive hypotheses about the factors that should influence the occurrence of tax amnesties. For our empirical test we rely on amnesty information from US states between 1981 and 2011. In line with the theoretical model, our empirical findings suggest that the likelihood of amnesties is mainly driven by a government's fiscal requirements and the taxpayers' expectations on future amnesties.
Keywords: 330; tax amnesties; strategic game; US states